Rhabdomyolysis following Nuss Procedure: A Prospective Study in Children - Estefanía, Karla; Serradilla, Javier; Ramirez, Carla; Velayos, Maria; Muñoz-Serrano, Antonio Jesus; Durán, Pilar; Fernández, Carlota; Hernandez, Francisco; De la Torre, Carlos (European Journal of Pediatric Surgery, 2022)
Introduction Postoperative rhabdomyolysis (RML) has been documented after several surgical procedures in adults. Musculoskeletal remodeling after Nuss procedure for pectus excavatum (PE) could cause RML. We evaluated the incidence of RML after Nuss procedure in children.Methods This study was a prospective study from 2018 to 2021. We enrolled all otherwise healthy patients who underwent PE correction with only one bar. Studied variables included demographic and clinical data, duration of surgery, complications, and length of hospitalization. The patients included underwent serial measurements of serum creatine kinase (CK), troponin I, N terminal pro B-type natriuretic peptide (NT-proBNP), serum creatinine, urea, and glomerular filtration rate at 6 and 48 hours postoperatively, and hospital discharge.Results Forty-six patients met criteria (40 males/6 females), with a mean age of 15.1 ± 1.4 years. Mean duration of surgery was 74 ± 28 minutes, and length of hospitalization was 4.6 ± 1.6 days. RML was diagnosed in 30.4% of patients at 6 hours, 91.3% at 48 hours, and 21.7% at hospital discharge. Mean preoperative CK value was 181.1 ± 141.6 IU/L, and postoperative values were 863.3 ± 302.6 IU/L at 6 hours, 1,675.2 ± 561 IU/L at 48 hours, and 850 ± 683.7 IU/L at hospital discharge, with statistically significant differences (p = 0.001). High-sensitivity troponin I and NT-proBNP levels increased significantly during the postoperative time (p = 0.001). Renal function remained stable (p = 0.55).Conclusion Nuss technique produces RML without kidney injury in healthy patients. This knowledge should be considered for patients at increased risk of developing acute kidney injury and other complications.
Keywords: rhabdomyolysis; pectus excavatum; creatine kinase